The prevalence of lateral incisors microdontia in students with Down syndrome - Mohammad Aziz, Nadia; Hartanto, Rudy; Soewondo, Williyanti (Universitas Padjadjaran, 2012)
Introduction: The term microdontia is used when the teeth are smaller than normal. It is recognized clinically as teeth having a usual crown shape or sometimes with tapering (peg or conical) crown in lateral incisors. Microdontia is usually manifested in systemic diseases and syndromes especially Down syndrome. The cause of microdontia is unknown but it could be multifactorial. The purpose of this research was to determine the prevalence of microdontia in patients with Down syndrome. Methods: Type of research is descriptive survey. The sampling method is purposive sampling. A study was conducted in 38 Down syndrome patients, aged between 7-29 years of age, consisted of 19 males and 19 females. The teeth were examined visually. Result: a total of 23 students had microdontia of lateral incisors of either the upper or lower jaw which indicated a prevalence of 60.53%. 10 students had microdontia of lateral incisors involving the upper and lower jaw which gives out a prevalence of 26.31%. Overall, the total prevalence of microdontia in the students with Down syndrome was 86.84%. Conclusion: Prevalence of microdontia in lateral incisors among patients with Down syndrome in Kota Bandung is high. There is no statistically significant difference in microdontia prevalence between female and male Down syndrome students.